Gliosarcomas lack BRAFV600E mutation, but a subset exhibit β‐catenin nuclear localization. Issue 5 (2nd March 2016) - Schwetye, Katherine E.; Joseph, Nancy M.; Al‐Kateb, Hussam; Rich, Keith M.; Schmidt, Robert E.; Perry, Arie; Gutmann, David H.; Dahiya, Sonika
Abstract : Gliosarcoma (GS) is a rare subtype of glioblastoma (GBM) characterized by both glial and mesenchymal components. Unlike GBM, there are no specific prognostic markers, and optimized treatments for patients with GS do not exist. Recent reports describe BRAF V600E mutation in malignant peripheral nerve sheath tumors, and aberrant Wnt signaling and CTNNB1 (β‐catenin gene) mutations have been described in GBM. We sought to determine whether GS tumors harbor BRAF V600E mutations or aberrant Wnt signaling, as indicated by nuclear localization of β‐catenin, by immunohistochemical detection. Forty‐eight (48) cases of primary and secondary adult GS (including recurrent ones) were evaluated by immunohistochemical techniques for the presence of nuclear β‐catenin and the BRAF V600E mutation. A small subset (6/46, 13%) showed nuclear localization of β‐catenin. None of the cases harbored BRAF V600E mutations (0/48). These results are the first to describe the presence of Wnt signaling pathway abnormalities, manifested by nuclear β‐catenin, in a subset, as well as the lack of BRAF V600E mutation in GS. We propose a potential role for Wnt pathway alterations in the pathogenesis of a subset of GS.